Work Risk Analysis in The Medical Records Storage (Filing) Room Using The Severity Assessment Method At Rsia Sitti Khadijah 1 Muhammadiyah Makassar Branch - Reski Dewi Pratiwi; Zahra Raihaniyah Ruslan; Mohammad Ardani Samad; Afriyana Amelia Nuryadin (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The process of storing medical records has risks that can threaten the safety and health of officers who are carrying out their work. Therefore, it is necessary to pay attention to occupational safety and health so as not to cause health problems and reduce the number of occupational risks. The aim of this research is to analyze work risks and determine how work risks are controlled in the filing room using the severity assessment method at RSIA Sitti Khadijah 1 Muhammadiyah Makassar Branch. This research used qualitative research methods. Data collection was conducted through interviews, observation, and documentation. Risk assessment determination will be evaluated using the severity assessment method. There are 8 risks found: 1 risk occurs very often, namely being exposed to dust with a moderate risk level; 5 risks often occur, namely being cut by files with moderate risk level, being hit by staples with moderate risk level, being hit by falling files with high risk level, slipping/spraining when taking files with high risk level, feeling pain when taking or inserting files with high risk level; 1 rare risk, namely accumulation of files with low risk level; and 1 very rare risk, namely patient documents being eaten by insects/termites on shelves with low risk level. The risk controls used to control risks at RSIA Sitti Khadijah 1 Muhammadiyah Makassar branch are elimination, substitution, personal protective equipment (PPE), and administration. For risk control, employees should use PPE such as gloves to minimize cuts and staple injuries, adjust file storage shelf sizes to Ministry of Health recommendations, clean rooms regularly to minimize risks such as respiratory problems due to dust in the storage room (filing) at RSIA Sitti Khadijah 1 Muhammadiyah Makassar branch.